A Research Framework for Investigating the Relationship between Safety Climate and Safety Performance in the Construction of Multi-storey Buildings in Pakistan. (2015) - Zahoor, Hafiz; Chan, Albert P.C.; Utama, Wahyudi P.; Gao, Ran
Abstract: Construction industry is contributing 2.39% to the GDP of Pakistan and is employing over four million people; however it is the second most injury prone industry, where employees often have to work under extreme weather conditions without taking precautionary measures. Construction of multi-storey buildings is at increase in the major cities where large and medium sized companies are working as main and sub-contractors; however these projects are suffering from fatal accidents, as safety measures are not rigorously enforced. This paper therefore presents a research framework to identify the safety climate factors which can significantly enhance the safety performance in the construction of multi-storey buildings. The quantitative data, split into calibration and validation sample, are being analyzed using exploratory and confirmatory factor analysis by examining the causal relationship between the safety climate and safety performance. Structured interviews and Delphi survey are being conducted to identify and prioritize; the causes of accidents, the impediments in the safety implementation, and the strategies to enhance the safety performance. The qualitative findings about neglected safety aspects are also discussed. Proposed safety climate measurement model would be useful to measure, monitor and improve the safety performance of construction companies in the developing countries.